Computing the Hough transform on a scan line array processor (image processing) - Fisher, A.L.; Highnam, P.T. (IEEE transactions on pattern analysis and machine intelligence, 1989)
A parallel algorithm for a line-finding Hough transform that runs on a linearly connected, SIMD (single-instruction, multiple-data-stream) vector of processors is described. The authors show that a high-precision transform, usually considered to be an expensive global operation, can be performed efficiently, in two to three times real time, with only local, communication on a long vector. The algorithm also illustrates a decomposition principle that has wide application in algorithm design for large linear arrays. A review of straight-line Hough transform implementations is also presented.< >